Effect of plant regulators on growth and flowering of 'Meyer' zoysiagrass - Marchi, S.r.; Martins, D. [UNESP]; Costa, N.v.; Silva, J.r.v. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2013)
This trial aimed to evaluate the effect of sequential applications of different plant regulators over growth and flower rachis emission of 'Meyer' zoysiagrass (Zoysia japonica). The study was conducted on 15-month old green turfgrass under a randomized complete block design with four replications. The following plant regulator and doses were tested: trinexapac-ethyl (113+113, 226+113, 226+226, 452+113, 452+226, 452+452, 678+339 e 904+452 g a.i./ha-1), prohexadione-calcium (100+100 e 200+200 g a.i. ha-1) and bispyribac-sodium (40+40 e 60+60 g a.i. ha-1), as well as an untreated control. The turfgrass was mowed again at 3.0 cm aboveground and the second plant regulator was applied when 'Meyer' zoysiagrass was between 5.0 and 6.0 cm high. The effect of the treatments was visually rated for visual injury, plant height, height and number of flower rachis, and total dry mass production of clippings. Only bispyribac-sodium had visual symptoms of injury on 'Meyer' zoysiagrass, and no intoxication was observed at 28 days after the second application (DAAB). The sequential applications of trinexapac-ethyl, prohexadione-calcium and bispyribac-sodium reduced by more than 80% the total clipping dry mass produced by 'Meyer' zoysiagrass. All the plant regulators tested also showed promising results in reducing the height and emission of rachis, especially when trinexapac-ethyl was applied at the doses 452+452, 678+339 and 904+452 g a.i. ha-1. 'Meyer' zoysiagrass turfgrass can be handled with the sequential application of a plant regulator, which reduces the need for mowing over a period up to 110 days after the application of the second plant regulator, and it also avoids deleterious visual effects over turfgrass.

Este trabalho teve o propósito de avaliar o efeito da aplicação sequencial de diferentes reguladores vegetais sobre o crescimento e a emissão de hastes florais da grama-esmeralda (Zoysia japonica). O estudo foi instalado em um gramado com 15 meses, no delineamento de blocos casualizados com quatro repetições, e os reguladores de crescimento e doses testados foram: trinexapac-ethyl (113+113, 226+113, 226+226, 452+113, 452+226, 452+452, 678+339 e 904+452 g i.a. ha-1), prohexadione-calcium (100+100 e 200+200 g i.a. ha-1) e bispyribac-sodium (40+40 e 60+60 g i.a. ha-1), além de uma testemunha sem aplicação de regulador de crescimento. Quando os tratamentos atingiram altura entre 5,0 e 6,0 cm, o gramado foi novamente aparado a 3,0 cm de altura, sendo em seguida realizada a aplicação da segunda dose dos reguladores. O efeito dos tratamentos foi avaliado quanto à fitointoxicação, por meio de avaliação visual, altura de plantas, altura e emissão de hastes florais e produção de massa seca de aparas. Apenas o bispyribac-sodium apresentou sintomas visuais de injúria, não se verificando mais intoxicação aos 28 dias após a segunda aplicação (DAAB). As aplicações sequenciais do trinexapac-ethyl, prohexadione-calcium e bispyribac-sodium apresentaram reduções acima de 80% na quantidade total de massa seca de aparas produzidas pela grama-esmeralda. Todos os reguladores de crescimento também demonstraram ser promissores em relação ao retardamento do crescimento e da emissão das inflorescências, com especial destaque para o trinexapac-ethyl aplicado nas doses de 452+452, 678+339 e 904+452 g i.a. ha-1. Gramados formados com grama-esmeralda podem ser manejados com a aplicação sequencial de regulador vegetal, com a redução da necessidade de cortes por um período de até 110 dias após a aplicação, além de não causar efeito deletério no aspecto visual sobre o gramado.
Efeito de reguladores vegetais sobre o crescimento e o florescimento de grama-esmeralda
Keywords: Zoysia japonica; trinexapac-ethyl; prohexadione-calcium; bispyribac-sodium; aplicação sequencial; Zoysia japonica; trinexapac-ethyl; prohexadione-calcium; bispyribac-sodium; sequential application